Evaluation of Advanced Nonlinear Static Procedure - Mohsen Ali Shayanfar (Iranian Society of Structrual Engineering (ISSE), 2015)
Having very simplicity, nonlinear static procedures (NSPs) are the most popular tools for estimation of structural capacity. These approaches construct a graphic display of the overall structural response via a pushover curve. The overall response of the system provides a direct simulation of the building as single degree of freedom (SDOF) system that simplifies the design and evaluation of the structure. In this research, the first step in any nonlinear static analysis or in other words perform a pushover analysis has been studied. Applied lateral load to the structural model not only affects the overall responses of the structure through structural capacity curve, but also directly affects the local responses of the structure. In order to evaluate these lateral loads, steel buckling restrained braced frame structures are examined by advanced modal pushovers. Next, the results of these pushover analyses will be compared with nonlinear time history analysis as the most accurate method. Finally, the most efficient method in this particular structure is introduced. The analysis conducted in these structures shows that the lateral load pattern based on story shears offers a good prediction of the maximum response of the concentrically buckling restrained braced frame buildings.